OPTIMASI KEPUTUSAN PEMBERIAN POTONGAN HARGA PRODUK AKSESORI MENGGUNAKAN METODE ARAS PADA DIANA ACCESSORIES - Nurul Fadhila (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Providing price discounts is an important marketing strategy to enhance product attractiveness and increase sales volume, especially in accessory businesses such as Diana Accessories. However, the process of determining which products deserve discounts is often carried out subjectively and is not based on structured criteria analysis. This study aims to optimize decision-making in granting discounts on accessory products by using the Additive Ratio Assessment (ARAS) method as a decision support system. The ARAS method is used to rank product alternatives based on several criteria. The criteria used in determining price discounts are limited to five main factors, namely: monthly sales level, stock quantity, profit margin (%), market demand, and product selling price, thereby providing a clearer basis in the evaluation process.The results show that the implementation of the ARAS method is able to provide more objective and accurate recommendations in determining discount priorities. The system developed also assists management in making decisions more quickly and efficiently.In conclusion, the ARAS method is effective in optimizing discount decision-making, thereby improving sales strategies and business competitiveness.